Analysis of Ethical Behavior, Perceive Organizational Support, Job Satisfaction, and Organizational Commitment on Employee Performance at PT Kilang Pertamina International, Cilacap, Central Java, Indonesia - Sofiansyah, Muhammad Edi; Siswanto, Agus; Sutanto , Aftoni (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of ethical behavior, organizational support, job satisfaction, and organizational commitment on employee performance at PT Kilang Pertamina International, Cilacap Unit. The research highlights how individual and organizational factors interact to shape work performance within the context of a strategic energy industry. A total of 270 respondents, selected through purposive sampling with a minimum of two years of tenure, participated in the survey. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with version 4.0, allowing for a rigorous assessment of both measurement validity and structural relationships among the constructs. The results indicate that all indicators demonstrate loading factors above 0.70, while the Average Variance Extracted (AVE) values range from 0.55 to 0.73, confirming the convergent validity of the constructs. In addition, the Composite Reliability (CR) values exceed 0.80, suggesting a high level of instrument reliability. The structural analysis further reveals that ethical behavior, organizational support, job satisfaction, and organizational commitment each exert a significant influence on employee performance. These findings not only reinforce prior literature concerning the role of behavioral and organizational factors in enhancing performance, but also provide practical implications for human resource management in the energy sector. Specifically, the study underscores the importance of fostering ethical practices, strengthening organizational support, and cultivating satisfaction and commitment as integral strategies for sustaining high levels of employee performance.